Backward partial vertical integration through private placement - Gonçalves, Ricardo (2023)
We analyze the market impact of a partial vertical integration whereby a subset of retail firms acquire, through a private placement operation, a non-controlling stake in the capital of an upstream firm, which supplies an essential input. In addition, we assume that this upstream firm can price discriminate between the retail firms which (now) own a stake in its capital and all of their retail rivals. We find that price discrimination is optimal and, compared to a vertical separation scenario, there is input foreclosure, a higher retail price, and lower social welfare, which suggests that, from a competition policy viewpoint, such partial vertical integrations should be analyzed with particular concern. On the other hand, incentives are such that conducting a private placement operation of the upstream firm’s capital yields gains from trade, and we are able to identify the optimal characteristics of such an operation.